Rozwój zrównoważony i jego nowe wyzwania - Jeżowski, Piotr (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2012)
Diverse perception of natural capital and sustainability in opposite approaches of environmental economics and ecological economics has impact on understanding and defining of sustainable development. Ecological economics approach based on strong and very strong sustainability is too ambitious for contemporary generation, although environmental economics approach based on weak sustainability is more realistic, but insufficient. Weaknesses of mainstream economics gave heterodoxy broad field for redefinition of sustainable development and for new synthesis for this socio-economic category. Demographic changes, duplication of Western consumption patterns in emerging economies and intensive pressure of global production and consumption on environment are the reasons why new agreements at international level on climate, energy, food security, access to clean water and protection other natural resources are needed. Effective coordination of actions and application of good governance standards taking into account such matters as human existential problems and needs, equity, access to information, social participation as well as indicators for sustainable development and green economy are also necessary,